Spectrum of glomerular diseases – clinico-pathologic observations from a state run tertiary care centre - Lingaraju, Umesha; Varma, Shyam S.; M.M., Satishkumar; V., Leelavathi; C.G., Shreedhar (International Journal of Research in Medical Sciences, 2017)
Background: Renal biopsy is an accurate tool for the diagnosis of glomerular disorders. This study was done to evaluate the histo-pathological spectrum of GDs at our centre and analyze its clinico-pathological correlation. Methods: All renal biopsies performed for suspected glomerular diseases at our institute over a period of 2 years from Jan 2013 to Jan 2015 were analyzed (n= 597). Biopsies were performed under ultrasound guidance and processed for light microscopy and immunofluorescence. Results: Among the total biopsies done, 597 (69.49%) had biopsy proven GD .The mean age of the patients included was 37.96 ± 15.58 years. M:F ratio was 2.3 : 1. The most common clinical syndrome was nephrotic syndrome (44.38%). PGDs were more common than SGDs The most common GD presenting as NS was FSGS (29.8%). Among patients with nephrotic syndrome, FSGS, MCD, and MGN predominated. DN was the commonest SGD, followed by Lupus nephritis. NDRD was reported in 33 patients (5.52%).Crescentic GN was seen in 11.89% cases majority presenting as RPGN. IgAN comprised 40.42% of the immune complex crescentic GNs. Amyloidosis was diagnosed in 1.84% of biopsies. Conclusion: Histo-pathological examination with LM and IF techniques and correlation with clinical, biochemical and serological markers as done in this study, have proved useful for the accurate diagnosis of glomerular diseases. It also provides important epidemiological information towards setting up a renal biopsy registry.